Initiation of an Enhanced Recovery After Cesarean Delivery Protocol in a University Hospital in Serbia: A randomized comparison with existing management (Pain medicine, 2023)
Background:  Enhanced Recovery After Surgery (ERAS) programs have been introduced in many  areas of clinical practice in recent years, to improve the patient’s recovery, increase patient satisfaction and shorten length of hospital stay. This study investigated feasibility of an ERAS protocol after cesarean delivery in a system where long-acting neuraxial opioids are not available. Materials and Methods: 200 parturients were randomly assigned to either an enhanced recovery group (E) or a control group (C) receiving standard care.  After delivery, parturients in group E received ultrasound guided quadratus lumborum block.  On the day of surgery, both groups received intravenous analgesia.  On the first post-operative day, patients in group E transitioned to oral analgesics, while group C continued intravenous analgesia.  On the second post-operative day, both groups received oral analgesics.  Data collected included total dose of analgesics used in the first 24 hours; pain scores at rest and with movement; patient satisfaction; and length of hospital stay. Six weeks after surgery, parturients received a questionnaire for postpartum depression assessment.Results: Group E reported better pain control with lower pain scores in all times (at rest and with movement), which was statistically significant, as was patient satisfaction.Conclusion:  Enhanced recovery protocols after cesarean delivery can improve postoperative recovery in low- and middle-income countries where long-acting neuraxial opioids may not be available.  Protocols need to be individually tailored for each institution in coordination with the health care system.
Keywords: obstetrics; cesarean section; enhanced recovery after surgery; analgesia